El Excentrico, 1970-05-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
May 5, 1970 [5 de mayo de 1970]. No volume or issue number. Cover has a cutout headshot of Ernest F. Abeytia for his election to the 25th Assembly District.